Bir ofis katının yapay zeka destekli doğal & yapay hibrid aydınlatma kontrolü - Abdullayev, Farhad (My University, 2021)
İç mekân çevre koşullarının insan sağlığı, memnuniyeti ve performansı üzerindeki etkileri onlarca yıldır araştırmaların odak noktası olmuştur. Mevcut çalışmalar, bilimsel performans ve algı, görme keskinliği ve reaksiyonu, hafıza, muhakeme ve emek üretkenliği üzerine çeşitli performans testleri içermektedir. Aydınlık, parlaklık oranı ve ilişkili renk sıcaklığının performansı farklı şekillerde etkilediği, deneysel tekniklerin, koşulların, kullanılan performans değerlendirme yöntemlerinin ve veri analizi yöntemlerinin etkisini yansıttığı bulunmuştur. Basit davranış ayarlamalarından, kapsamlı ev iyileştirmelerine kadar, evlerin, ofislerin enerji kullanımını azaltmanın birçok farklı yolları vardır. Enerjiyi korumanın iki ana nedeni, elektrik faturalarından tasarruf etmek ve çevreyi korumaktır. Kapalı alanlarda enerji tasarrufu sağlamanın en yayğın yolları: günlük davranışların ayarlanması, ampullerin değişmesi, akıllı güç şeritlerinin kullanılması, enerji açışından verimli cihazların satın alınmasıdır. Enerji tasarrufu birçok nedenden dolayı önemli ve faydalıdır. Basit enerji tasarrufu önlemleri mülk değerinin artmasına ve çevrenin korunmasına yardımçı olmaktadır.

The effects of indoor environmental conditions on human health, satisfaction and performance have been the focus of research for decades. Current studies included various performance tests on cognitive performance and perception, visual acuity and reaction, memory, reasoning, and labor productivity. It was found that luminance, brightness ratio and associated color temperature affect performance in different ways, reflecting the effect of experimental techniques, conditions, performance evaluation methods and data analysis methods. There ae many different ways to reduce the energy use of homes and offices, from simple behaviour to comprehensive home improvements. The two main reasons for conserving energy are saving the electricity bills and protecting the environment. The most common ways to save energy in confined spaces: adjusting daily behaviour, changing light bulbs, using smart power strips, purchasing energy efficient appliance and so on. Energy saving is important and beneficial for many reasons Simple energy saving measures can help increase value and protect the environment.Meteorological weather conditions may show sudden changes (cloud movements, dust) regionally, regardless of the seasons. In this study, control outputs are produced because of comparing both perceived sensors and national meteorological data so that temporary (sudden regional change) sky movements do not cause rapid changes in the system. The Artificial Intelligence supported design to control the light pipe (LP) & LED hybrid lighting system real-time application is modeled. The study aims to increase energy savings and to guide academic studies in this field.
Keywords: Artificial intelligence; Electric; Electronics; Elektrik; Elektronik; Gün ışığı aydınlatması; Hibrit aydınlatma; Hybrid lighting; MIMO ANN; Sustainable lighting; Sürdürülebilir aydınlatma Daylight harvesting; Yapay zeka